Applying Alternative Assessment to Endorse and Optimize Student Engagement and Student Performance in Second Language Learning - Hensman, C.A. (University of Jaffna, 2018)
Assessments are part and parcel of Teaching and Learning process as they play a pivotal role in evaluating and assessing student performance. Teaching and learning have become so engrossed with assessments and assessments have become so common nowadays as learners are often involved in various types of assessments throughout their entire study programme. The names of the assessments may vary, but the ways in which they are conducted remain traditional in most instances. This naturally triggers out a sense of detest among the learners, still they are compelled to complete what is assigned for them before the due dates, as failing to do an assignment will affect their final marks. As a result, the real potential of the learners remains hidden and intangible as their efforts are without passion. As an attempt to overcome this gap, the researcher attempts to apply a new mode of operation – the Alternative assessment methods, so that the new venture might open up new spirit in learners which ultimately functions as a catalyst to embark the real potential of the learners. The study has adopted mixed method approach -qualitative as well as quantitative methodology. The findings of the research are fruitful and the researcher is looking forward to apply the new intervention to sow the seeds of enthusiasm among the students
Keywords: Adapt; alternative; assessment; engross; enthusiasm; student engagement